Flow and Heat Transfer of Williamson Hybrid Ferrofluid with Combined Convective Transport - Mokhtar, Masyfu’ah; Mohd Kasim, Abdul Rahman; Nordin, Nur Syahidah; Waini, Iskandar (Akademi Baru, 2023)
The present research investigated the characteristics of combined convective blood flow carrying copper and magnetite nanoparticles over a shrinking sheet, modelled as Williamson hybrid ferrofluid. The mathematical model is converted to similarity equations by suitable transformations. The similarity equations are then solved using the bvp4c function. The characteristics and effects of Williamson and combined convective transport parameter, as well as the nanoparticle volume fraction in the Williamson hybrid ferrofluid towards the temperature profiles, velocity profiles as well as the Nusselt number and the skin friction coefficient are analysed and discussed. Outcomes reveal the increment in Williamson parameter suppress the heat transfer performance of the fluid but not for the combined convective transport and suction parameter. Meanwhile the heat transfer performance is also improved as concentration of copper is increased.